Students’ Thinking Process in Constructing the Concepts of Linear Quantities Two Variables - , Kusno, A.Mujib MT. Sunardi (International Journal of Scientific Research and Management (IJSRM), 2017)
This reseach aimed at analyzing the students’ thinking process in cunstructing the concepts of linear quantities two variables. The participants were 6 students of grade 8 on junior high school in Jember Regency, East Java Indonesia. It focused on three concepts, i.e definition concept, modelling, and Linear Quantities Two Variables (LQTV) solving. Participants are given question that includes it the concepts. The result show that 2 participants succeed in constructing definition concepts, 4 participants succeed in constructing modelling concept, and 1 participants succed in constructing solving concept. Participants’ thinking process in constructing LQTV concepts consisted of 3 steps, i.e: planning, monitoring, and evaluation. Generally, participants’ thinking proccess were categorized into three types, i.e type A consist of planning (activating relevant facts, selecting goal, and selecting strategies), monitoring, and evaluation; type B consist of planning (selecting goal, activating relevant facts, and selecting strategies), monitoring, and evaluation; type C consist of planning (activating relevant facts, selecting goal, selecting strategies, activating relevant facts, and selecting strategies), monitoring, and evaluation.